2019
DOI: 10.1016/j.vas.2019.100057
|View full text |Cite
|
Sign up to set email alerts
|

Causes of adult mortality in two populations of New Zealand sea lions (Phocarctos hookeri)

Abstract: Highlights Infectious disease, including tuberculosis, was the most common cause of death. Anthropogenic trauma caused 26% of deaths in mainland sea lions. Trauma inflicted by adult male conspecifics caused 24% of deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Hypermucoviscous K . pneumoniae disease has only ever been recorded in the pup age class (< approximately 3 months) of NZ sea lions, despite routine necropsies of adults and juveniles that die at Enderby Island during the field season and on mainland NZ throughout the year [24]. One brief reference to an adult male NZ sea lion found dead at the Catlins, mainland NZ, in 2003 with a pharyngeal abscess described a culture of K .…”
Section: Discussionmentioning
confidence: 99%
“…Hypermucoviscous K . pneumoniae disease has only ever been recorded in the pup age class (< approximately 3 months) of NZ sea lions, despite routine necropsies of adults and juveniles that die at Enderby Island during the field season and on mainland NZ throughout the year [24]. One brief reference to an adult male NZ sea lion found dead at the Catlins, mainland NZ, in 2003 with a pharyngeal abscess described a culture of K .…”
Section: Discussionmentioning
confidence: 99%
“…Without access to the resources and infrastructure that modern life affords for many people, these threats often lead to pain and death. For example, in a study of 136 New Zealand sea lions, 18% of them were found to die from tuberculosis and 24% died as a result of violence from other sea lions (Lenting et al, 2019). Similarly, approximately half of American black bears die as cubs due to causes such as disease, infanticide, and drowning in their winter dens as a result of flash flooding (Alt, 1984;Elowe & Dodge, 1989;LeCount, 1987).…”
Section: Measuring Attitudes Towards Wild Animal Welfare: the Wild An...mentioning
confidence: 99%